Women and the framed-novelle sequence in eighteenth-century England: clothing instruction with delight - Rozell, C (2012)
English women writers of the eighteenth century manifested enthusiasm for a form best described as a framed-novelle sequence, that is, a form in which conversations between characters/narrators are interspersed with embedded narratives. This thesis argues that the framed-novelle, with its distinctive juxtaposition of narrative and critical conversation facilitated feminine intervention in the period’s political, social, and literary debates. It demonstrates that Delarivier Manley, Jane Barker, Eliza Haywood, Sarah Scott, Sarah Fielding and Jane Collier used the framed-novelle sequence to develop a feminine but nonetheless authoritative socio-critical voice which allowed them not only to intervene in contemporary literary debates about the risks and rewards of reading fictions (especially with regards to the wider significance of the feminocentric and apparently trivial matter of amatory, romantic tales)but also to construct timely argument about the effect of fictional exemplarity on readers. Consideration of the literary and cultural contexts of the framed-novelle’s production, specifically its relation to other forms of narrative sequences such as the oriental tale and the fairy tale collection and to the period’s ideals of sociable conversation and critical practice also allows this thesis to identify the framed-novelle’s importance within the larger field of eighteenth-century literary development. Through close readings in each main chapter of an earlier and later framed-novelle by each author, this thesis explores the distinctiveness and internal cohesion of the framed-novelle as a subgenre, while also recognizing the particularity of each writer’s protofeminist perspective on their accumulation of feminocentric tales.